STRATEGI KOMUNIKASI PADA PELESTARIAN KESENIAN TRADISIONAL SRANDUL - Ni Putu Widyasari; Sri Yuwanti (Lembaga Pengembangan Kinerja Dosen, 2022)
One of the national cultures of Srandul is recorded as a folk performance art originating from Yogyakarta. Diera today, especially in the younger generation, many are not familiar with traditional arts, especially Srandul, which has faded its existence. Many factors are the cause of the lack of public interest in traditional arts, one of which is the lack of information provided about traditional arts and technological advances that are not accompanied by readiness to compete with outside cultures, making local cultures begin to fade in demand. This research uses a qualitative approach and selects the types of data collection carried out in this study are observation, interviews and documentation. The communication strategy by using festivals as a medium in conveying efforts to preserve Srandul traditional art will be appropriate and in accordance with the younger generation who are targeted